Z dziejów Galerii Akademii Sztuk Pięknych w Krakowie (Krzysztofory. Zeszyty Naukowe Muzeum Historycznego Miasta Krakowa, 2026)
FROM THE HISTORY OF THE ACADEMY OF FINE ARTS GALLERY IN CRACOW, ON THE ANNIVERSARY OF ITS CLOSINGThe history of the Academy of Fine Art Gallery in Cracow, called the museum from 1985, begins with the beginnings of this, Poland’s oldest arts university, in 1818, as in that year the School of Painting and Drawing was created within the Department of Philosophy and Letters of the Cracow Academy. Both chairs, painting and drawing, were occupied by the creators of the design and organizational structure of the school, painters Józef Brodowski and Józef Peszka. Right away, plaster casts began to be collected, gradually enriched by donations and purchases, to form an interesting collection. As the school became independent and detached from the University, and with changes in the curriculum, paintings also were gathered. The history of the Gallery at the Academy of Fine Arts not only illustrates the development of the school, its trends or artistic styles, but also is perfect proof of changes in teaching methods. Unfortunately, it has proven as well that the school rectors of directors did not care enough for the heritage of generations. They did not succed in making the gallery at the Academy a museum to rank with Vienna, to make the dreams of the Academy’s founder a reality. Up to the present time the collection has remained without proper academic supervision, in a place not adapted to function asa museum storage, while a decision of the Rector’s Council of the Academy of Fine Arts has halted all activities of this institution.